Intramolecular Propargylic Ene Reaction of Benzyne En Route to Highly Functionalized Allenes and Allenamides - Tawatari, Tsukasa; Kato, Ritsuki; Takasu, Kiyosei; Takikawa, Hiroshi (Synthesis, 2022)
A variety of highly functionalized allenes and allenamides are prepared by intramolecular propargylic ene reactions of benzynes. Specific benzyne precursors having a chlorodiisopropylsilyl group serve as platforms to link with various propargyl alcohols via a Si–O bond, thereby expanding the scope of this reaction. Also demonstrated is a complete transmission of point to axial chirality to give a chiral, non-racemic allenamide.
Keywords: ene reaction; intramolecular reaction; benzyne; allenes; allenamides